Financial Development and Economic Growth in Cemac Countries (Global Journal of Management and Business Research, 2012)
The main aim of this research work is to determine the relationship that exists between financial development and the growth rate of per capita real GDP in CEMAC countries using panel data estimation techniques. It emphasises the reciprocal impact of financial development on growth in order to determine the type of relationship that exist and make policy recommendations.To do this, we measured financial development and economic growth with the liquidity rate and the growth rate of per capita real GDP respectively.We tested these two measures in a static panel model using Ordinary Least Squares (OLS) for the first model and Feasible Generalised Least Squares (FGLS) for the second. Based on the results obtained from data on these countries for the period from 1980 to 2006, we established that financial developmentnegatively affects economic growth and that the inverse positive relationship is not significant.These results, coupled with those of Granger causality test, allow us to show that there exists a unidirectional causality running from economic growth to financial development in CEMAC countries. We concluded by making policy recommendations in order to ameliorate this relationship.
Keywords: CEMAC; financial development; economic growth; panel data; direction of relationship